Prawomocność czy integracja? Studia porównawcze działalności politycznej na uchodźstwie - Goddeeris, Idesbald (Pamięć i Sprawiedliwość, 2010)
Exiles, defined as refugees or immigrants engaging themselves in opposition politics against their homeland, have been studied quite thoroughly. This research, however, does rarely exceed the frameworks of national history, treating exiles only as the trailblazers of the nation’s current political system. Only a few scholars have approached exile politics in a more systematic and comparative way. Their research, though, concentrates on exiles claiming legitimacy (governments in exile, national committees), while the political activities of other exiles seem to have been more influential.